Mode Bifurcation on Contact Line Dynamics at Oil/Water Interface Depending on the Contact Line Length - Yamamoto, Daigo; Maeno, Jumpei; Manabe, Yuki; Okamoto, Yasunao; Nawa-Okita, Erika; Shioi, Akihisa (Frontiers in Chemistry, 2021)
The motion of the contact line at the oil/water interface caused by chemical reactions is well known as a typical example of artificial active matter in the field of nonlinear science. When water (containing trimethylstearylammonium chloride) and nitrobenzene (containing iodide anion) phases are in contact, the regulated traveling-wave patterns appear along the inner wall of the glass container. In this study, we demonstrate a new dynamical mode of the contact line, an up-and-down motion, which becomes dominant with the decrease in the size of a glass tube, and the probability of occurrence is extremely high when the diameter of the glass tube is below 1 mm. A physicochemical model of the contact line motion that incorporates the spatiotemporal variation of the surfactant concentration on a glass surface is proposed, and its effect on the wettability of oil/water phases on the walls of the glass tubes is studied. The present model can reproduce the mode bifurcation of the dynamical motion depending on the inner diameter of the glass tubes.